1995
DOI: 10.1111/j.1365-2958.1995.mmi_17020333.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple homologues of LuxR and LuxI control expression of virulence determinants and secondary metabolites through quorum sensing in Pseudomonas aeruginosa PAO1

Abstract: In Pseudomonas aeruginosa PAO1, expression of elastase is dependent upon an interaction between the positive transcriptional activator LasR and the auto-inducer molecule N-(3-oxododecanoyl)-L-homoserine lactone (OdDHL), the synthesis of which is directed by LasI. Previously we have shown that in PAN067, an elastase-negative mutant of PAO1, elastase production can be restored to some extent by addition of exogenous N-(3-oxohexanoyl)-L-homoserine lactone (OHHL). Here we report that PAN067 is also defective in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
402
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 446 publications
(404 citation statements)
references
References 38 publications
1
402
0
1
Order By: Relevance
“…It has been shown recently that the RsmA in A. vinelandii represses post-transcriptionally the expression of PhbR, a transcriptional regulator that activates the phbBAC operon encoding the PHB-synthesis enzymes (Hernandez-Eligio et al, 2012). In the case of P. aeruginosa PAO1, however, it has been suggested that the GacS/GacA TCS regulates the production of AHLs, which have a positive effect upon the induction of rpoS expression, which in turn activates genes expressed mainly during the stationary phase, such as those encoding the production of several virulence factors, including pyocyanine, exotoxin A, elastase and lipase enzymes and type III secretion system among others (Hogardt et al, 2004;Latifi et al, 1995;Reimmann et al, 1997;Winson et al, 1995;Winzer et al, 2000). Furthermore, it has been reported that this signal transduction system in this bacterium acts exclusively by controlling the transcription of the RsmY and RsmZ regulatory small RNAs (Brencic et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown recently that the RsmA in A. vinelandii represses post-transcriptionally the expression of PhbR, a transcriptional regulator that activates the phbBAC operon encoding the PHB-synthesis enzymes (Hernandez-Eligio et al, 2012). In the case of P. aeruginosa PAO1, however, it has been suggested that the GacS/GacA TCS regulates the production of AHLs, which have a positive effect upon the induction of rpoS expression, which in turn activates genes expressed mainly during the stationary phase, such as those encoding the production of several virulence factors, including pyocyanine, exotoxin A, elastase and lipase enzymes and type III secretion system among others (Hogardt et al, 2004;Latifi et al, 1995;Reimmann et al, 1997;Winson et al, 1995;Winzer et al, 2000). Furthermore, it has been reported that this signal transduction system in this bacterium acts exclusively by controlling the transcription of the RsmY and RsmZ regulatory small RNAs (Brencic et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Various Gram-negative bacteria (e.g. Vibrio fischeri, Pseudomonas aeruginosa and Vibrio anguillarum) produce multiple acyl-HSL molecules with various N-acyl side-chains (Kuo et al, 1994;Latifi et al, 1995;Milton et al, 1997). To determine whether E. chrysanthemi produces one or more acyl-HSLs, an ethyl acetate extract from the culture supernatant of strain 3937 was fractionated by thin-layer chromatography (TLC).…”
Section: E Chrysanthemi Strain 3937 Produces Multiple Pheromonesmentioning
confidence: 99%
“…One commonly occurring example is antimicrobials. Quorum-controlled antimicrobials have been described in many saprophytic Proteobacteria including Erwinia carotovora (Bainton et al, 1992), Pseudomonas aeruginosa (Kownatzki et al, 1987;Bainton et al, 1992;Gallagher and Manoil, 2001;Ran et al, 2003;Schuster and Greenberg, 2006), Burkholderia thailandensis (Bt) and Chromobacterium violaceum (Cv) (Latifi et al, 1995;McClean et al, 1997). Although some groups have proposed that antimicrobial activity of secondary metabolites is a side effect and the primary function of these compounds is as signals (Davies et al, 2006;Yim et al, 2007), the classic view is that they are used for competition with other strains or species in multi-species environments.…”
Section: Introductionmentioning
confidence: 99%